P-249 The role of hospices in the emerging world of integrated and devolved health and care systems. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Dewar, Steve; Taylor, Judy; Harries, John; Wilson, Janet; Wilsher, Amanda
Abstract : Background: Strengthening the leadership of hospice care is one of five key steps identified by the Commission into the Future of Hospice Care to ensure that hospices are fit for the future. The landscape for hospice leaders is complex and challenging. The majority of hospices have seen their statutory funding remain static or even fall. The demand for end-of-life care is predicted to increase significantly and NHS and local authorities are urging local leaders to develop end of life care systems that are integrated, accessible, systematic and responsive. To meet these challenges, hospice leaders need a coherent story about the role of their organisations in the future, their capacity to contribute to new systems of care and their ability to lead complex change. Hospice leaders on the Hospice UK Strategic Leadership Programme will be identifying key features of this future landscape for hospice care. The 2016 Conference provides an exciting opportunity to share their emerging vision for the future with the wider hospice community. Aims: Hospice leaders on the Strategic Leadership Programme will be exploring the national landscape of end-of-life care and shaping their own response to the challenges. The aim is to bring these responses to the challenges to the 2016 conference, to stimulate debate and inspire leadership across the sector. Methods: During the first two modules of the Strategic Leadership Programme a cohort of over 30 hospice leaders from more than 20 hospices will develop an understanding of the potential and compelling narratives necessary for the future success of the hospice movement. Conclusion: Sharing these narratives at the Hospice UK Conference will provide an opportunity for the wider hospice sector to react and help shape the story that will inform the future leadership aspirations of a new cohort of hospice leaders.